2020
DOI: 10.1016/j.bjpt.2019.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Physical therapy and migraine: musculoskeletal and balance dysfunctions and their relevance for clinical practice

Abstract: Background: Migraine is a primary headache with high levels of associated disability that can be related to a variety of symptoms and comorbidities. The role of physical therapy in the management of migraine is largely unknown. Therefore, the aim of this review is to highlight and critically discuss the current literature and evidence for physical therapy interventions in individuals with migraines. Methods: A narrative review of the literature was performed. Results: Physical therapists assessing and treating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 178 publications
0
40
0
10
Order By: Relevance
“…Therefore, this could support the hypothesis that SMFR could become an important technique to manage altered balance that is one of the accompanying symptoms. 28 Values detected for cervical ROM showed a lightly trend in increase for the left rotation (p= 0.09). It is known that migraine is associated with muscle pain in the neck region and patient who suffered of this disorder adopt an antalgic posture modifying the cranio-cervical posture.…”
Section: Resultsmentioning
confidence: 90%
“…Therefore, this could support the hypothesis that SMFR could become an important technique to manage altered balance that is one of the accompanying symptoms. 28 Values detected for cervical ROM showed a lightly trend in increase for the left rotation (p= 0.09). It is known that migraine is associated with muscle pain in the neck region and patient who suffered of this disorder adopt an antalgic posture modifying the cranio-cervical posture.…”
Section: Resultsmentioning
confidence: 90%
“…Peripheral and central sensitisation are states of the nervous system that are frequently discussed in relation to chronic pain conditions including migraine (5254) and altered sensory responses of migraine patients in the cervical musculoskeletal region have been reported (6,55,56). In the previous stratification study (22), a correlation was found between headache frequency and pain provocation on palpation indicating that patients with a pain response were more affected.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of pain and dysfunction in the cervical area are often veri ed in patients with migraine. [1][2][3][4] Evidence has shown that these patients present a reduction of the cervical range of motion, 4-8 motor control alterations and changes in the performance of the cervical muscles. 9,10 However these aspects may not be equally observed for all migraineurs.…”
Section: Introductionmentioning
confidence: 99%
“…It is established that patients with chronic migraine present a greater prevalence of neck dysfunction including articular, muscular and sensitivity aspects compared to episodic migraine. 3,[8][9][10] According to the International Headache Society, 11 migraine can also be classi ed according to the presence of aura. This phenomena is present in one-third of the patients, preceding or accompanying a migraine attack.…”
Section: Introductionmentioning
confidence: 99%